2009
DOI: 10.1515/cclm.2009.281
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian glycogen storage disease type III – identification of six novel AGL mutations, including a large 1.5 kb deletion and a missense mutation p.L620P with subtype IIId

Abstract: Background: Glycogen storage disease type III (GSD III) is caused by mutations in AGL which encodes for a single protein with two enzyme activities: oligo-1, 4-1, 4-glucantransferase (transferase) and amylo-1, 6-glucosidase. Activity of both enzymes is lost in most patients with GSD III, but in the very rare subtype IIId, transferase activity is deficient. Since the spectrum of AGL mutations is dependent on the ethnic group, we investigated the clinical and molecular characteristics in Egyptian patients with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This is the second mutation described in Tunisian patients. Previously, Lucchiari et al reported a homozygous W1327X substitution located in exon 31 of AGL gene in Tunisian GSD III patient living in Italy (11,22) which also have been reported in Egyptian patients (18).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is the second mutation described in Tunisian patients. Previously, Lucchiari et al reported a homozygous W1327X substitution located in exon 31 of AGL gene in Tunisian GSD III patient living in Italy (11,22) which also have been reported in Egyptian patients (18).…”
Section: Discussionmentioning
confidence: 73%
“…Sixteen SNPs in AGL gene were determined, as described previously (18). SNPs numbers were cited according to database of SNPs (dbSNP Build 130) available from http://www.ncbi.nlm.nih.gov/SNP/.…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic variation is common among patients with different genotypes who have glycogen storage disease type IIIa. 1,3,11,16,17 In adults, the condition may only be diagnosed late once hepatomegaly, cirrhosis, hepatic carcinoma, cardiomyopathy or neuro-muscular dysfunction has developed. 18 Clinical variability among patients with the same mutation could be related to the age at diagnosis, compliance with dietary recommendations, environment or unknown modifying genes.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the AGL gene encoding glycogen debranching enzyme have been described in many populations, including Northern European, 2 Egyptian, 3 Hispanic 2 and Asian; 2 a high prevalence of the disease was also found in the North African Jewish community (1/5400) and in the Faroe Islands (1/3600). 4,5 We previously described the presenting clinical characteristics of 4 Inuit children with putative glycogen storage disease type III and suspected the presence of a founder effect.…”
mentioning
confidence: 99%
“…IVS32-12A>G mutation in AGL gene was defined in a Japanese GSD IIIb patient for the first time and studies conducted later showed the presence of very different types of mutations (2,3,4,5,6,7,8,9). Although most mutations have been reported only for once, at least four different recurrent mutations have been found in AGL gene (5,10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%